May Underdiagnosed Nutrition Imbalances Be Responsible for a Portion of So-Called Unexplained Infertility? From Diagnosis to Potential Treatment Options. (June 2016) - Noventa, Marco; Quaranta, Michela; Vitagliano, Amerigo; Cinthya, Vescio; Valentini, Romina; Campagnaro, Tania; Marci, Roberto; Paola, Rossana Di; Alviggi, Carlo; Gangemi, Michele; Saccardi, Carlo; Nardelli, Giovanni Battista; et al.
The aim of the study was to investigate whether women affected by unexplained infertility may have undiagnosed dietary imbalances which negatively affect fertility. Secondarily, we investigated whether varying degrees of nutritional abnormalities may benefit from different periconceptional dietary supplementations, evaluating the most effective intervention in improving pregnancy rate after in vitro fertilization (IVF). We conducted a survey on 2 cohorts of patients (group A: unexplained infertility and group B: healthy first trimester spontaneous pregnancies) with the scope of investigating and comparing their dietary status discriminating women without dietary abnormalities (cohort 1) from those with abnormalities exclusively in micronutrient intake (cohort 2) or combined abnormalities in both micronutrient and macronutrient intake and associated obesity (cohort 3). All women included in group A were offered the opportunity to receive a prescription for one of the 3 designated daily dietary supplementation schemes (subgroups A1, A2, and A3) which were to be implemented in the 3 months immediately prior to beginning IVF treatment. When compared with fertile women, patients having unexplained infertility showed significant abnormalities in dietary habits. These differences ranged from a minimal imbalance in micronutrient intake (potentially avoidable with dietary supplementation) to severe combined macronutrient and micronutrient imbalance frequently associated with obesity (partially amendable by inositol supplementation and frequently requiring long-term dietary reeducation before establishment of fertility). Nutritional investigation and treatment may explain and resolve a portion of cases of unexplained infertility, improving the outcome of IVF treatment and, with minimal imbalances, likely restore spontaneous fertility.